Constructing an integrated problem-based and collaborative learning model: Empirical research on the development of fourth-grade primary school students' problem-solving and teamwork skills in mathematics class - Xie, Lei; Charatkamolpong, Suwisa; Kanjanakate, Supawadee (Asian Journal of Contemporary Education, 2025)
In the 21st - century skills - oriented education, this study aims to bridge the gap in traditional mathematics teaching, which often addresses teamwork and problem - solving skills independently. It focuses on designing and assessing an integrated instructional model using Problem - Based Learning (PBL) via Collaborative Learning (CL) to equip students with integrated skill sets. A quasi - experimental single - group pretest/posttest study was carried out with 30 fourth - grade students. They participated in well - designed instructional activities, and their skills were measured using standardized instruments before and after the intervention. The results showed significant improvements in students' teamwork and problem - solving skills. Teamwork skills had a mean increase of 5.17 points (p < 0.05), and problem - solving skills improved by 3.10 points (p < 0.05). PBL and CL are effective in engaging students in divergent thinking, collaborative learning, and solving real - world problems. This empirically - validated instruction provides educators with a roadmap to develop key competencies for students' academic and career success, offering solutions to improve primary mathematics education for all - round student development.